Simulation in Neonatal Resuscitation - Garvey, Aisling A.; Dempsey, Eugene M. (Frontiers in Pediatrics, 2020)
Approximately one in ten newborns will require basic resuscitation interventions at birth. Some infants progress to require more advanced measures including the provision of positive pressure ventilation, chest compressions, intubation and administration of volume/ cardiac medications. Although advanced resuscitation is infrequent, it is crucial that personnel adequately trained in these techniques are available to provide such resuscitative measures. In 2000 Louis Halmalek and colleagues called for a ‘New Paradigm in Pediatric Medical Education: Teaching Neonatal Resuscitation in a Simulated Delivery Room Environment’. This was one of the first articles to highlight simulation as a method of teaching newborn resuscitation. The last decades have seen an exponential growth in the area of simulation in newborn care, in particular in newborn resuscitation and stabilisation. Simulation is best defined as an instructional strategy “used to replace or amplify real experiences with guided experiences that evoke or replicate substantial aspects of the real world in a fully interactive manner”. Simulation training has now become an important point of how we structure training and deliver improved healthcare to patients. Some of the key aspects of simulation training include feedback, deliberate practice, outcome measurement, retention of skills and curriculum integration. The term ‘Train to win’ is often used in sporting parlance to define how great teams succeed. The major difference between sports teams is that generally their game day comes once a week, whereas in newborn resuscitation every day is potentially ‘game day’. In this review we aim to summarise the current evidence on the use of simulation based education and training in neonatal resuscitation, with particular emphasis on the evidence supporting its effectiveness. We will also highlight recent advances in the development of simulation based medical education in the context of newborn resuscitation to ensure we ‘train to win’.